2010
DOI: 10.1002/jcb.22579
|View full text |Cite
|
Sign up to set email alerts
|

Targeted disruption of Nemo‐like kinase inhibits tumor cell growth by simultaneous suppression of cyclin D1 and CDK2 in human hepatocellular carcinoma

Abstract: The Wnt/beta-catenin signaling pathway regulates various aspects of development and plays important role in human carcinogenesis. Nemo-like kinase (NLK), which is mediator of Wnt/beta-catenin signaling pathway, phosphorylates T-cell factor/lymphoid enhancer factor (TCF/LEF) factor and inhibits interaction of beta-catenin/TCF complex. Although, NLK is known to be a tumor suppressor in Wnt/beta-catenin signaling pathway of colon cancer, the other events occurring downstream of NLK pathways in other types of canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 29 publications
4
52
0
Order By: Relevance
“…It has been reported that NLK was significantly overexpressed in the HCC specimens compared to corresponding normal tissues in Korean patients [12]. In order to further confirm the results above and explore the physiological or pathological relationship between expression of NLK and proliferation index Ki-67 in HCC samples in Chinese patients, we first detected the levels of NLK and Ki-67 in a series of 136 HCC tissues by immunohistochemical staining.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…It has been reported that NLK was significantly overexpressed in the HCC specimens compared to corresponding normal tissues in Korean patients [12]. In order to further confirm the results above and explore the physiological or pathological relationship between expression of NLK and proliferation index Ki-67 in HCC samples in Chinese patients, we first detected the levels of NLK and Ki-67 in a series of 136 HCC tissues by immunohistochemical staining.…”
Section: Resultsmentioning
confidence: 83%
“…Furthermore, expression of NLK was also significantly upregulated in HCC specimens compared to corresponding normal tissues in Korean patients, based on the Western blot analysis and RT-PCR of five selected HCCs and corresponding normal tissues and immunohistochemical analysis of TMA containing 30 HCCs and 20 normal tissues. Targeted disruption of NLK could inhibit the proliferation of Hep3B cells and arrest cell cycle transition [12].…”
Section: Introductionmentioning
confidence: 99%
“…Targeted deletion of NLK can suppress the growth of hepatocellular carcinoma through inhibition of CDK2 and Cyclin D1, suggesting that NLK may play a role in promoting the growth of hepatoma cells by promoting cell cycle progression (Jung et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…NLK is an evolutionary conservative kinase and exerts its diverse function in embryonic patterning, nervous system development, and human cancers due to its capacity to regulate signaling, including Wnt/b-catenin, Notch, IL6, and activin (36,(40)(41)(42). NLK is known to phosphorylate LEF1, a key transcription factor in the Wnt signaling pathway at Thr155 and Ser166 residues (34).…”
Section: Discussionmentioning
confidence: 99%